Dichotomous Effects of Mu Opioid Receptor Activation on Striatal Low-Threshold Spike Interneurons - Elghaba, Rasha; Bracci, Enrico (Frontiers in Cellular Neuroscience, 2017)
Striatal low-threshold spike interneurons (LTSIs) are tonically active neurons that express GABA and nitric oxide synthase and are involved in information processing as well as neurovascular coupling. While mu opioid receptors (MORs) and their ligand encephalin are prominent in the striatum, their action on LTSIs has not been investigated. We addressed this issue carrying out whole-cell recordings in transgenic mice in which the NPY-expressing neurons are marked with green fluorescent protein (GFP). The MOR agonist [D-Ala(2),N-MePhe(4),Gly-ol]-enkephalin (DAMGO) produced dual effects on subpopulations of LTSIs. DAMGO caused inhibitory effects, accompanied by decreases of spontaneous firing, in 62% of LTSIs, while depolarizing effects (accompanied by increase in spontaneous firing) were observed in 23% of LTSIs tested. The dual effects of DAMGO persisted in the presence of tetrodotoxin (TTX), a sodium channel blocker or in the presence of the nicotinic acetylcholine receptor antagonist mecamylamine. However, in the presence of either the GABAA receptor antagonist picrotoxin or the muscarinic cholinergic receptor antagonist atropine, DAMGO only elicited inhibitory effects on LTSIs. Furthermore, we found that DAMGO decreased the amplitude and frequency of spontaneous GABAergic events. Unexpectedly, these effects of DAMGO on spontaneous GABAergic events disappeared after blocking of the muscarinic and nicotinic cholinergic blockers, showing that GABA inputs to LTSIs are not directly modulated by presynaptic MORs. These finding suggest that activation of MORs affect LTSIs both directly and indirectly, through modulation of GABAergic and cholinergic tones. The complex balance between direct and indirect effects determines the net effect of DAMGO on LTSIs.